Traumatic subdural hematoma in a 10-month-old infant. Case report and literatue review - Lourdes María Fernández García; Rodolfo Javier Rivero Morey (Universidad de Ciencias Médicas de Granma, 2021)
Introduction: Head injuries constitute a major global public health problem, with an approximate incidence in the general population of 500 million per year. Head trauma can cause physical or mental sequelae such as emotional disturbances, amnesia, anxiety, depression, attention deficit, and other psychiatric disorders, as well as disability and death. Objective: To inform the pediatric community about a case of subdural hematoma secondary to moderate traumatic brain injury in the infant. Case Presentation: The case of a 10-month-old infant who was brought to the hospital due to a blow to the head after a fall is presented. He was admitted and interpreted as a mild head injury with a negative neurological physical examination. The next day, the boy began to show low interaction, presented vomiting and two convulsive events, decided to perform an urgent CT scan of the skull, and diagnosed a right frontoparietal subdural hematoma. Conclusions: Any health problem can be considered a priority if it occurs frequently or if it is very serious. Traumatic brain injuries are the leading cause of death in children over one year of age in developed countries, also causing mental retardation, epilepsy and physical disability. Its early diagnosis and correct treatment are of vital importance to ensure the survival of the patient.